Prevalence of bed falls among inpatients in Iranian hospitals: A meta-analysis - Parvaneh Isfahani; Mohammad Sarani; Mina Salajegheh; Somayeh Samani; Aliyeh Bazi; Mahdieh Poodineh Moghadam; Fatemeh Boulagh; Mahnaz Afshari (Human Factors in Healthcare)
Background: Falling out of hospital beds can reduce patients’ satisfaction, increase their length of stay and mortality, reduce hospital productivity, and increase health system costs. The present research aimed to determine the prevalence of bed falls among inpatients in Iranian hospitals. Methods: This study was a meta-analysis. All the articles on the prevalence of bed fall in Iranian hospitals were extracted from five databases as well as the Google Scholar search engine and their quality was assessed. The heterogeneity of the studies was tested using the I2 index and the meta-regression model at the 0.05 significance level. Finally, the Comprehensive Meta-Analysis software analyzed six articles that met the inclusion criteria. Results: Based on the estimation of a random effects model, the prevalence of bed falls in Iranian hospitals was 19.9 % (7.7 %-42.6 %; 95 % CI). The highest prevalence was observed in Kermanshah province in 2014 at 92 % (80.5 %-97.0 %; 95 % CI) and the lowest prevalence was observed in Tabriz in 2015 at 6 % (3.4 %-10.4 %%; 95 % CI). Moreover, there were significant relationships between sample size, average age, and the prevalence of bed falls among inpatients (p < 0.05). Conclusions: The findings indicate that the prevalence of bed falls is high among hospitalized patients in Iran, with considerable implications for patient safety and healthcare costs. Addressing this issue requires targeted interventions focusing on environmental safety, staff training, and patient education to mitigate fall risks effectively.